2017
DOI: 10.1111/jar.12429
|View full text |Cite
|
Sign up to set email alerts
|

Explicit and implicit attitudes towards people with intellectual disabilities: The role of contact and participant demographics

Abstract: The results encourage more implicit-explicit attitude relationship research regarding disability. The associations between demographics, contact and implicit attitudes should be explored further. Research should question whether implicit attitudes reflect participants' true beliefs-denoting less importance to demographics-or whether they reflect wider societal values rather than individuals' attitudes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Although most previous studies that have investigated whether social desirability affects self-reported attitudes to people with ID found no such bias [ 26 ], it cannot be guaranteed that the results are a genuine reflection of respondents’ attitudes or their likelihood to behave in certain ways in real life situations. There is some evidence that explicit attitudes differ from implicit attitudes [ 44 ], but more research needs to be done on studying implicit attitudes and on examining the relationship between self-reported attitudes and actual behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Although most previous studies that have investigated whether social desirability affects self-reported attitudes to people with ID found no such bias [ 26 ], it cannot be guaranteed that the results are a genuine reflection of respondents’ attitudes or their likelihood to behave in certain ways in real life situations. There is some evidence that explicit attitudes differ from implicit attitudes [ 44 ], but more research needs to be done on studying implicit attitudes and on examining the relationship between self-reported attitudes and actual behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Murch et al investigated the community attitudes to individuals with mental disabilities in the US in light of demographic variables. It was shown that such attitudes differed according to the level of education, age and degree of kinship [10]. Fleming et al in his research compared between mothers of children with autism and mothers of those with mental disabilities.…”
Section: J Edu and Learnmentioning
confidence: 99%
“…This influence is a result of acquaintance with a disabled person and the resulting emotions and behavior toward him/her. Knowledge about a population of individuals with IDD . It was found that a positive relationship exists between knowledge of IDD individuals’ skills and positive attitudes toward them (Murch et al., 2018). Socialization .…”
Section: Psychological Empowerment Self-efficacy and Positive Attitudes Toward Individuals With Idd In The Mentoring Processmentioning
confidence: 99%
“…Knowledge about a population of individuals with IDD. It was found that a positive relationship exists between knowledge of IDD individuals' skills and positive attitudes toward them (Murch et al, 2018). 5.…”
Section: Positive Attitudes Toward Individuals With Iddmentioning
confidence: 99%